A2A Adenosine Receptor Antagonism Enhances Synaptic and Motor Effects of Cocaine via CB1 Cannabinoid Receptor Activation - Tozzi, Alessandro; de Iure, Antonio; Marsili, Valentina; Romano, Rosaria; Tantucci, Michela; Di Filippo, Massimiliano; Costa, Cinzia; Napolitano, Francesco; Mercuri, Nicola Biagio; Borsini, Franco; Giampà, Carmen; Fusco, Francesca Romana; et al. (PLOS ONE, 2012)
Background Cocaine increases the level of endogenous dopamine (DA) in the striatum by blocking the DA transporter. Endogenous DA modulates glutamatergic inputs to striatal neurons and this modulation influences motor activity. Since D2 DA and A2A-adenosine receptors (A2A-Rs) have antagonistic effects on striatal neurons, drugs targeting adenosine receptors such as caffeine-like compounds, could enhance psychomotor stimulant effects of cocaine. In this study, we analyzed the electrophysiological effects of cocaine and A2A-Rs antagonists in striatal slices and the motor effects produced by this pharmacological modulation in rodents. Principal Findings Concomitant administration of cocaine and A2A-Rs antagonists reduced glutamatergic synaptic transmission in striatal spiny neurons while these drugs failed to produce this effect when given in isolation. This inhibitory effect was dependent on the activation of D2-like receptors and the release of endocannabinoids since it was prevented by L-sulpiride and reduced by a CB1 receptor antagonist. Combined application of cocaine and A2A-R antagonists also reduced the firing frequency of striatal cholinergic interneurons suggesting that changes in cholinergic tone might contribute to this synaptic modulation. Finally, A2A-Rs antagonists, in the presence of a sub-threshold dose of cocaine, enhanced locomotion and, in line with the electrophysiological experiments, this enhanced activity required activation of D2-like and CB1 receptors. Conclusions The present study provides a possible synaptic mechanism explaining how caffeine-like compounds could enhance psychomotor stimulant effects of cocaine.